Agrarian Inequality and Civil War Revisited. Issue 8 (August 2015) - Gutierrez, Francisco
Abstract The paper maps the trajectory of the proposition according to which agrarian inequality is somehow associated with the onset and persistence of civil wars. This proposition was dominant in many disciplines in the 1960s and 1970s but was radically challenged by economic/individualistic interpretations of war, which forced it out from the research agenda. However, it has made a strong comeback, allowing many classical themes to be reconsidered. But the present way of linking agrarian inequality to civil war involves new themes and a more complex political economy of violent conflict, as well as different understandings of the relevant inequalities and of the role of institutions, actors, and space. This, in turn, poses complex research questions and methodological challenges.